Faktor yang Berhubungan dengan Insidens Penyakit Gastritis di Puskesmas Ranotana Weru Kota Manado - Kireina G. S. Rumengan; Theo. W. E. Mautang; Prycilia P Mamuaja (Yayasan Syalom Cipta Sumikolah, 2025)
Gastritis is one of the most common digestive tract diseases with a high prevalence in Indonesia, including in Manado City. It is often associated with lifestyle factors such as irregular eating patterns, stress, use of non-steroidal anti-inflammatory drugs (NSAIDs), and frequent consumption of spicy and acidic foods. This study aims to identify the factors associated with the incidence of gastritis at Ranotana Weru Public Health Center, Manado City. This research used a quantitative approach with a case-control design. The sample consisted of 52 respondents (26 gastritis cases and 26 controls) selected through purposive sampling. Data were collected using questionnaires and analyzed with the chi-square test. The statistical analysis showed a significant relationship between eating patterns (p = 0.047) and drug consumption (p = 0.031) with the incidence of gastritis. However, no significant relationship was found between stress (p = 0.107), consumption of spicy and acidic foods (p = 0.162), gender (p = 0.205), and age (p = 0.378) and the incidence of gastritis. Poor eating habits and drug consumption are factors associated with the incidence of gastritis. Health promotion interventions regarding proper diet and careful use of medications are essential to prevent increased gastritis cases in the community.